Commentary on The impact of a postoperative oxygen therapy protocol on use of pulse oximetry and oxygen therapy [original article by Komara JJ Jr. et al appears in RESPIR CARE 1995;40(11):1125-9]. - Ruggles L (AACN Nursing Scan In Critical Care)
PURPOSE: To investigate the clinical and financial impact of a postoperative oxygen therapy protocol on patient management practices. METHOD: A nonrandom sample of postoperative patients (N = 40) was divided into two groups. In Group 1, O2 therapy was managed by physicians; in Group 2, O2 therapy was managed by respiratory therapists using a standard protocol with a stop criterion of room air pulse oximetry saturation (SPO2) >/=92%. FINDINGS: Statistically significant differences were noted between groups on both per patient costs of O2 therapy ($27.94 vs. $7.84) and pulse oximetry ($18.64 vs. $7.84). The average duration of O2 therapy in Group 1 was 3.45 days (SD 1.28) compared to 2.1 days (SD 0.64) in Group 2. In Group 1, 16 patients continued to receive O2 therapy after attaining the room-air SPO2 Stop criterion used in Group 2. No adverse outcomes related to hypoxemia were reported in either group. CONCLUSIONS: Use of a uniform stop criterion for low-flow O2 therapy in postoperative management of nonthoracic surgical patients could safely shorten the duration of O2 therapy and reduce the number of pulse oximetry measurements. [Original article accession number: 1996002383 (algorithm, research, tables/charts)]